Ammonia oxidation intermediates-induced abiotic transformation of 17α-ethinylestradiol in nitrification process of wastewater biological treatment. Issue 4 (August 2022) - Wang, Lili; Jiang, Xiaoman; Li, Anjie
Abstract: 17α-Ethinylestradiol (EE2) has aroused growing concern due to its increasing worldwide prevalence and high ecotoxicological risk. It has been reported that the removal of EE2 in the nitrification process of wastewater treatment plants (WWTPs) is attributed to co-metabolism induced by ammonia oxidizers. However, the effect of ammonia oxidation intermediates produced by ammonia oxidizers on the abiotic transformation of EE2 is unclear. In this study, the effect of several ammonia oxidation intermediates, including free nitrous acid (FNA), hydroxylamine (NH2 OH), and nitric oxide (NO) on the abiotic transformation of EE2 was evaluated comprehensively. The dynamics of EE2 transformation induced by FNA were affected by the FNA concentration and the initial EE2 concentration. During EE2 nitration induced by FNA, 2, 4-nitro-EE2 would be the final nitration product of EE2. FNA-mediated transformation of EE2 was effective for reducing estrogenicity and the transformation was stable under decreased FNA levels or during refrigeration at 4 °C. The key reactive nitrogen species derived from the FNA-induced EE2 nitration reaction have been verified to be nitrogen dioxide (NO2 ) and/or NO by using a scavenger. Under acidic conditions, NO2 was inferred to be the key reactive nitrogen species inducing the nitration reaction of EE2. As an ammonia oxidation intermediate or FNA-derived species, NO can transform EE2 under alkaline conditions. Unlike FNA and NO, NH2 OH could not transform EE2. These findings provide a deeper understanding of the abiotic transformation mechanism of EE2 induced by ammonia oxidation intermediates, exhibiting a significant value in the removal of micropollutants during ammonia oxidation in WWTPs. Graphical Abstract: ga1 Highlights: EE2 nitration could be affected by FNA concentration and EE2 initial concentration. The estrogenicity of EE2 nitration products was lower than the parent compound. EE2 nitration was stable under FNA concentration decrease or refrigeration at 4 ℃. Key reactive nitrogen species from FNA for EE2 nitration should be NO2 and (or) NO. As an ammonia oxidation intermediate, NH2 OH could not transform EE2 abiotically.